AN ANNOTATED TRANSLATION OF A NOVEL ENTITLED THE GREAT PATRIOTIC WAR OF THE SOVIET UNION - I Nyoman Adnyana (Populis : Jurnal Sosial dan Humaniora, 2019)
AbstractThis research is about annotated translation with the object a novel entitled The Great Patriotic War of the Soviet Union written by Joseph Stalin. The problems of this research are: (1) What are the difficulties encountered by the researcher in translating the source text? and (2) How are those difficulties solved in the translation? The aims of this research are: (1) To identify the difficulties encountered by the translator in translating the source text; and (2) How the difficulties are solved which include strategies in translating the source text.  In conducting this annotated translation, the researcher employed introspective and retrospective methods. The researcher analyzed 25 annotations of problems out of 100 items of data related to lexicon, grammatical structure, communication situation, and cultural context, and revealed that there were 17 lexicons, 7 grammatical structures, 1 communication situation. Those difficulties which, at the same time, had become problems were analysed to attain solutions in accordance with the relevant translation strategies and translation theories, namely: descriptive translation, naturalization, paraphrasing, addition, deletion, cultural equivalent. The finding of this research can be concluded that translation theories are still needed or even they are very important in the process of translation to produce a good translation. Appropriate translation theories, methods, and procedures can overcome translation problems.